Analisis Pengaruh Komunikasi Dan Komitmen Organisasi Terhadap Prestasi Kerja Karyawan di PT. BPR Perbaungan Hombar Makmur - Asmarolita Manurung (Institute of Computer Science (IOCS), 2019)
Maintaining relationships with employees requires effective communication. In addition, the commitment of employee organizations is an important issue, because the problem of mobility and the level of employee exit directly affects the quality of company services. Employees who have a strong organizational commitment to the company and have loyalty at work will try to continue to develop themselves in order to improve their work performance. Data collection techniques are done by interview, questionnaire and study documentation. The data analysis method used is multiple linear regression using SPSS Version 17.00 software. The sample in this study were all employees of PT. BPR Perbaungan Hombar Makmur, amounting to 32 people. The results of the hypothesis test show that communication and organizational commitment together influence the work performance of employees of PT. BPR Perbaungan Hombar Makmur. And partially communication is more dominant than organizational commitment. The conclusions in this study are 1) communication influences the work performance of employees of PT. BPR Perbaungan Hombar Makmur 2) Organizational commitment influences the work performance of PT. BPR Perbaungan Hombar Makmur. 3) communication and organizational commitment together affect the work performance of employees of PT. BPR Perbaungan Hombar Makmur.